Ralphcannonite, AgZn2TlAs2S6, a new mineral of the routhierite isotypic series from Lengenbach, Binn Valley, Switzerland. (2nd January 2018) - Bindi, Luca; Biagioni, Cristian; Raber, Thomas; Roth, Philippe; Nestola, Fabrizio
Abstract: The new mineral species ralphcannonite, AgZn2 TlAs2 S6, was discovered in the Lengenbach quarry, Binn Valley, Wallis, Switzerland. It occurs as metallic black equant, isometric to prismatic crystals, up to 50 μm, associated with dufrénoysite, hatchite, realgar and baryte. Minimum and maximum reflectance data for COM wavelengths in air are [λ (nm): R (%)]: 471.1: 25.8/27.1; 548.3: 25.2/26.6; 586.6: 24.6/25.8; 652.3: 23.9/24.8. Electron microprobe analyses give (wt.%): Cu 2.01(6), Ag 8.50(16), Zn 10.94(20), Fe 3.25(8), Hg 7.92(12), Tl 24.58(26), As 18.36(19), Sb 0.17(4), S 24.03(21), total 99.76(71). On the basis of 12 atoms per formula unit, the chemical formula of ralphcannonite is Ag0.63(2) Cu0.25(2) Zn1.35(5) Fe0.47(1) Hg0.32(2) Tl0.97(3) [As1.97(6) Sb0.01(1) ]Σ1.98(5) S6.03(8) . The new mineral is tetragonal, space group I 42 m, with a = 9.861 (2), c = 11.125(3) Å, V = 1081.8(4) Å 3, Z = 4. The main diffraction lines of the calculated powder diagram are [ d (in Å), intensity, hkl ]: 4.100, 85, 211; 3.471, 40, 103; 2.954, 100, 222; 2.465, 24, 400; 2.460, 39, 303. The crystal structure of ralphcannonite has been refined by X-ray single-crystal data to a final R1 = 0.030, on the basis of 140 observed reflections [ F o > 4σ( F o )]. It shows a three dimensional framework of (Ag, Zn)-centred tetrahedra (1 M 1 + 2 M 2), with channels parallel to [001] hosting TlS6 and (As, Sb)S3 disymmetric polyhedra. Ralphcannonite is derived from its isotype routhierite M1 Cu M2 Hg2 TlAs2 S6 through the double heterovalent substitution M1 Cu + + M2 Hg 2+ → M1 Zn 2+ + M2 Ag + . This substitution obeys a steric constraint, with Ag +, the largest cation relative to Zn 2+ and Cu +, entering the largest M 2 site, as observed in arsiccioite. The ideal crystal-chemical formula of ralphcannonite is M1 Zn M2 (Zn0.5 Ag0.5 )2 TlAs2 S6 .